Multimodal Analysis of Action Movie Poster - Muhammad Azis Saputra; Rusdi Noor Rosa (English Language and Literature, 2020)
The aim of this study was to find the multimodal analysis used in Man of Steel and Avengers Infinity Wars movie posters. The Method used in this study is a descriptive qualitative method. This research used theory semiotic approach which focuses on multimodal system proposed by Cheong (2004). The researcher found 6 types elements of multimodal in Man of Steel and Avengers Infinity Wars posters such as material, behavioral, mental, identifying, attributive, and intensive. The data were collected by analysis the movie posters. They were 30% on material, 15% on behavioral, 15% on mental, 15% on identifying, 10% on attributive, and 15% on intensive in Man of Steel poster. Meanwhile in Avengers Infinity Wars poster, the research found 40% on material, 5% on behavioral, 15% on mental, 10% on identifying, 10% on attributive, 20% on intensive.